Using local and indigenous ecological knowledge to examine local-scale perceptions, effects of, and resilience and adaptation to, climate change on human/landscape interactions on the Pacific coast of North America - Wyllie de Echeverria, VR (2019)
The aims of this research were to investigate the perceptions and impacts of climate change on the ecological and cultural aspects of landscape through understanding local and Indigenous knowledge. Key cultural and ecological species were chosen for study by bridging Traditional Ecological Knowledge (TEK) and western scientific knowledge in a constructive, equitable, and practical way. These Cultural Keystone Indicator Species (CKIS) provide a novel and cross-culturally meaningful analytical framework for investigating the socio-ecological effects of environmental change.